ТАРИЙХ САБАҚЛАРЫНДА ТАРИЙХЫЙ ДЕРЕКЛЕРДЕН ПАЙДАЛАНЫЎ УСЫЛЛАРЫ - Баўетдинов, Р.А. (FAN va JAMIYAT, 2018)
The article is devoted to the study of issues of effective using of historical sources. There is an analysis of the methods of using historical sources. The author emphasizes the positive influence of historical sources in increasing the quality and outcome of the lesson.